2020
DOI: 10.1016/j.actbio.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate co-immobilized with cRGD ligands and BMP2 on biomimetic platforms promotes BMP2-mediated osteogenic differentiation

Abstract: Heparan sulfate co-immobilized with cRGD ligands and BMP2 on biomimetic platforms promotes BMP2mediated osteogenic differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 77 publications
6
18
0
Order By: Relevance
“…We have also shown that bBMP-2 presented from a soft film was sufficient to trigger cell spreading and migration 26 , overriding the response to film stiffness. The same effect has been shown on rigid surfaces with a low cRGD surface density 27 and on surfaces presenting peptides specific for α5β1 integrins 28 . This process on soft films involved 3 integrins and BMP receptors that worked together to control SMAD signaling and tensional homeostasis 26 , thereby coupling cell adhesion and fate commitment.…”
Section: Introductionsupporting
confidence: 71%
“…We have also shown that bBMP-2 presented from a soft film was sufficient to trigger cell spreading and migration 26 , overriding the response to film stiffness. The same effect has been shown on rigid surfaces with a low cRGD surface density 27 and on surfaces presenting peptides specific for α5β1 integrins 28 . This process on soft films involved 3 integrins and BMP receptors that worked together to control SMAD signaling and tensional homeostasis 26 , thereby coupling cell adhesion and fate commitment.…”
Section: Introductionsupporting
confidence: 71%
“…We have also shown that bBMP-2 presented from a soft film was sufficient to trigger cell spreading and migration 26 , overriding the response to film stiffness. The same effect has been shown on rigid surfaces with a low cRGD surface density 27 and on surfaces presenting peptides specific for α5β1 integrins 28 . This process on soft films involved β3 integrins and BMP receptors that worked together to control SMAD signaling and tensional homeostasis 26 , thereby coupling cell adhesion and fate commitment.…”
Section: Introductionsupporting
confidence: 71%
“…The role of 1 integrin in osteoblastic differentiation is recognized, but appears to depend on the cell type and on the context. Previously in our group, Sefkow-Werner et al found an activator role of 1 integrin with sBMP-2 and BMP-2 bound to heparan sulphate, by using also C2C12 cells 27 . Many data have shown that 1 integrin plays an important role in osteoblast differentiation and function [56][57][58] .…”
Section: Identification Of Integrins In Bmp-induced Cell Adhesion Andmentioning
confidence: 71%
“…It is commonly known that some behaviors and functions of cells are related to the performances of proteins absorption on implantable materials [ 36 ]. These adsorbed proteins could serve as ligands to bind to cell membrane protein receptors (integrins) leading to cell/materials adhesion [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known that some behaviors and functions of cells are related to the performances of proteins absorption on implantable materials [ 36 ]. These adsorbed proteins could serve as ligands to bind to cell membrane protein receptors (integrins) leading to cell/materials adhesion [ 36 ]. For example, Fn plays a vital role in the initial cell adhesion and spreading on materials, because it can specially bind to integrins on cell membranes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%